2013
DOI: 10.1093/abbs/gmt006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of <italic>Mst1</italic> overexpression on the growth of human hepatocellular carcinoma HepG2 cells and the sensitivity to cisplatin <italic>in vitro</italic>

Abstract: Mammalian STE20-like kinase 1 (Mst1) is the mammalian homologue of Drosophila Hippo, a major inhibitor of cell proliferation in Drosophila. It ubiquitously encodes serine threonine kinase that belongs to the family of protein kinases related to yeast STE20, and is involved in cell proliferation, apoptosis, oncogenesis, and organ growth. Recent studies have shown that Mst1 has tumor-suppressor function, and the deletion or mutation of Mst1 is reported to be associated with tumorigenesis. To investigate the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 47 publications
5
12
0
Order By: Relevance
“…MST1 gene abnormalities are commonly observed in colorectal (13,14), hepatocellular (11,15) and gastric (16) cancer. It has also been found that the expression of YAP in the Hippo pathway is elevated in human primary colorectal cancer (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MST1 gene abnormalities are commonly observed in colorectal (13,14), hepatocellular (11,15) and gastric (16) cancer. It has also been found that the expression of YAP in the Hippo pathway is elevated in human primary colorectal cancer (17).…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al (10) found that mice lacking MST1/2 could not inhibit the proliferative and anti-apoptotic activity of the carcinogenic gene YAP1, resulting in the formation of liver cell carcinoma. However, subsequent to the transfection of MST1 into HepG2 cells, MST1 was re-expressed, resulting in the loss of the proliferative activity of YAP1, the promotion of apoptosis and the elimination of tumorigenicity (11). …”
Section: Introductionmentioning
confidence: 99%
“…These results and our results suggest that YAP plays an important role in human HCC. Moreover, the idea that the overexpression of YAP leads to HCC development was confirmed by experiments in YAP transgenic mice [17]. …”
Section: Discussionmentioning
confidence: 99%
“…MST1 overexpression not only decreases cell proliferation but also induces apoptosis of the human breast cancer cell line MCF-7. Moreover, the overexpression of MST1 can inhibit cell proliferation and promote the cytoplasmic localization and phosphorylation of YAP (Ser127) protein, which may be one of the tumor inhibitory mechanisms of the MST1 gene [30,31]. Consistent with the major roles of MST in cell proliferation and apoptosis, LATS regulates the balance between proliferation and differentiation during adipose development.…”
Section: Introductionmentioning
confidence: 99%